An expedient synthesis of 2-aryl-1,4-benzoxazin-3-ones via tandem Anionic cyclisation/alkylation reactions of N-Boc-O-benzyl-2-aminophenols - Bodero,O; Spivey,AC (Synlett, 2016)
A one-pot, tandem anionic cyclization/alkylation reaction of N-Boc-O-benzylated-2-aminophenols to give 2-aryl-1,4-benzoxazin-3-ones is described. The Boc protecting group plays a crucial role in the process, as the tert-butoxide liberated in the cyclisation step facilitates the benzylic deprotonation necessary for the subsequent alkylation. The reaction gives expedient access to a range of substitution patterns in 1,4-benzoxazin-3-ones of potential biological relevance.